Size and Shape Distribution of Microplastics in PET Recycled Wastewater and Their Removal Behavior during the Coagulation–Flocculation Process - Fadlilah, Lilya Irsianti; Ardeline, Mela; Lasmita, Revi (Journal of Engineering Science and Technology Management (JES-TM), 2025)
Plastic Recycling Facilities (PRFs), although intended to reduce plastic pollution, can act as potential sources of microplastic release due to mechanical processing activities. This study aims to investigate the size and shape distribution of microplastics in polyethylene terephthalate (PET) recycling wastewater and to evaluate their removal behavior through coagulation–flocculation processes. Wastewater samples were collected from several treatment stages of the wastewater treatment system at a PET recycling facility. The results indicate that microplastics are predominantly fragment-shaped, with medium-sized particles representing the most abundant fraction. Coagulation–flocculation was shown to effectively remove microplastics, particularly fragment-shaped and medium-sized particles, compared to film and fiber forms. Removal efficiency was influenced by microplastic size and shape characteristics. These findings suggest that coagulation–flocculation has strong potential as an effective method for controlling microplastic release from PET recycling wastewater and provides a basis for developing more targeted wastewater treatment strategies.